Epidemiological profile of patients hospitalized with Crohn’s disease due to severe acute respiratory infection during the COVID-19 pandemic: a 2-year report from Brazil - Nascimento, Laís Silva; Marson, Fernando Augusto Lima; dos Santos, Raquel de Cássia (Frontiers in Medicine, 2024)
The novel coronavirus-induced severe acute respiratory syndrome resulted in one of the most significant global pandemics of the 21st century, posing substantial challenges to healthcare systems worldwide, including those in Brazil. This study aimed to investigate the demographic and clinical profiles of hospitalized patients with both coronavirus disease (COVID)-19 and Crohn's disease in Brazil over two years. Methods: An epidemiological analysis was conducted utilizing data collected from Open-Data-SUS. The study focused on describing the demographic characteristics, clinical manifestations, comorbidities, and hospitalization details of patients afflicted with severe acute respiratory syndrome due to COVID-19 and Crohn's disease to predict the chance of death. Results: The States of São Paulo, Paraná, and Minas Gerais were responsible for 50% of the COVID-19 cases. The most affected racial group was that of individuals who self-declared as mixed race. The most prevalent comorbidities were heart disease, diabetes mellitus, and obesity. The most affected age group was 25 to 60 years old, especially in hospitalized patients with Crohn's disease and COVID-19 who succumbed. A multivariable analysis was conducted to describe the risk factors associated with the likelihood of classifying patients with CD into the groups with a higher chance of death. In brief, the predictors of death were a) the presence of neurological disorder (OR=6.716; 95%CI=1.954-23.078), b) the need for an intensive care unit (OR=3.348; 95%CI=1.770-6.335), and c) need for invasive mechanical ventilatory support (OR=59.017; 95%CI=19.796-175.944). Conclusions: Gender did not show a discernible prevalence among hospitalized patients with Crohn's disease and COVID-19; however, individuals of mixed race were disproportionately affected. The 25-60 age bracket emerged as the most susceptible demographic group, presenting high risks of hospitalization and mortality. Moreover, the study underscores the potential for COVID-19 to induce systemic pathologies with long-term degenerative effects and sequelae.